Role of morphological traits and cell wall components in imparting resistance to pink stem borer, Sesamia inferens Walker in maize - Soujanya, P. Lakshmi; Sekhar, J. C.; Karjagi, Chikkappa G.; Ratnavathi, C. V.; Venkateswarlu, R.; Yathish, K. R.; Suby, S. B.; Sunil, N.; Rakshit, Sujay (Frontiers in Plant Science, 2023)
Host Plant Resistance (HPR) is the most important component for sustainable management of insect pests. The present work was aimed to understand the role of various morphological and biochemical factors as defense mechanism and their interaction on different biological parameters attributed to survival and development of pink stem borer in maize. The resistant and moderately resistant genotypes (DMRE 63, CM 500 and WNZ Exotic pool) suffered least leaf injury rating (LIR), dead hearts (DH%), percentage stem tunneling (ST%), number of entry/exit holes (E/EH) as compared to susceptible ones (CM 202 and BML 6). The variation in morphological traits such as number of nodes, internode distance and stem diameter could not distinguish all the resistant genotypes from that of susceptible genotypes in terms of its mean value. Higher levels of biochemical constituents, viz., p-Coumaric acid (p-CA), ferulic acid (FA), acid detergent fibre (ADF) and acid detergent lignin (ADL) were observed in resistant genotypes compared to susceptible ones. Antibiosis was expressed in terms of reduced pupal weight when fed on WNZ Exotic pool, whereas larval weight and larval survival affected when fed on DMRE 63. Higher concentration of p-CA content in pith of resistant maize genotypes prolonged the pupal period of pink stem borer. Higher concentration of p-CA and FA contents in rind reduced the adult emergence, as they showed significant negative correlation between them. The larval period was prolonged with higher levels of ADF and ADL contents in maize genotypes either in rind or both rind and pith as both ADF and ADL content showed a significant positive correlation with the larval period. The correlation coefficients between p-CA with DH (%), ST (%) and E/EH were r= -0.9642**, r= -0.9363**, and r= -0.9646**, respectively. Similarly, the correlation coefficients between FA with DH (%), ST (%) and E/EH were r= -0.9217*, r= -0.9563**, and r= -0.9434**, respectively and ADF with DH (%), ST (%) and E/EH were r= -0.9506**, r= -0.9611**, and r= -0.9709**, respectively. The findings obtained can be utilised in pink stem borer resistance breeding programmes to enhance and diversify the basis of resistance.